A THERMOELASTIC ANALYSIS USING THE BOUNDARY ELEMENTS, DIC AND THERMAL IMAGES - Oberg, Matheus B. A. M.; Anflor, Carla T. M. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The main goal of this work relies on developing an experimental procedure to verify a thermoelastic Boundary Elements Method (BEM) analysis using imaging techniques for obtaining the steady-state displacement and temperature fields on isotropic solids. The experimentally obtained temperature field is used as input for the numerical BEM analysis in order to represent the thermal expansion effect. The domain’s temperature and consequent resultant thermoelastic displacement fields are carried into the BEM formulation using the Radial Integration Method (RIM). This method consists in a mathematical technique where the radial basis functions are applied to convert domain integrals to the boundary. The use of the RIM avoids the necessity of domain discretization and, therefore, preserves the BEM advantages. For this method to be effective, the experimentally obtained field that describes the temperature difference between the initial and final temperatures on the domain is described by a forth order polynomial. In the end, the resultant numerical displacement field, obtained from the experimental temperature field and the BEM analysis, is compared to the experimental displacement data in order to evaluate the numerical method efficacy. The verified proximity between the obtained numerical displacement curves and its experimental equivalents indicates the good performance of the proposed methodology.